2018
DOI: 10.1007/s11625-018-0556-3
|View full text |Cite
|
Sign up to set email alerts
|

The success of transdisciplinary research for sustainable land use: individual perceptions and assessments

Abstract: Evaluation is a major issue in discussions of transdisciplinary research (TDR). Empirical studies often consider expert perspectives; however, knowledge of the experiences, attitudes, and motivations of a broader science-practice community applying transdisciplinarity remains rare. The present study aims to gather insights into the perceptions and assessments of success of TDR projects from scientists and practitioners with experience with TDR processes. Based on a mixed-method approach combining qualitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…However, it is obvious that a lack of science/policy interfaces represents a crucial barrier of knowledge exchange (Barrier 4). Clearly, this finding is strongly in line with the literature on transdisciplinarity (Zierhofer and Burger 2007;Zscheischler et al 2018).…”
Section: Barriers To Knowledge Exchangesupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is obvious that a lack of science/policy interfaces represents a crucial barrier of knowledge exchange (Barrier 4). Clearly, this finding is strongly in line with the literature on transdisciplinarity (Zierhofer and Burger 2007;Zscheischler et al 2018).…”
Section: Barriers To Knowledge Exchangesupporting
confidence: 90%
“…Gibbons et al (1994: 1) also observed that the modes of knowledge production had been changing. From their point of view, knowledge is no longer solely produced disciplinarily and in a context of mainly scientific interests (Mode 1 knowledge production), but also transdisciplinarily and in "a context of application" (Mode 2 knowledge production) (Gibbons et al 1994: 3-5;Zscheischler et al 2018). However, there has been a shift not only in the way knowledge is produced and who is involved in this process, but also in the way knowledge is exchanged (Bielak, Campbell, Pope, Schaefer, and Shaxson, 2008): referring to the findings of Funtowicz and Ravetz (1993), Gibbons et al (1994) and Pretty and Chambers (1993), Bielak et al (2008: 202 et seq.…”
Section: Introductionmentioning
confidence: 99%
“…61 Such reflection may not be practised enough. 91 Meetings Regular meetings are important to foster crossdisciplinary working 9 23 29 31 38 55-57 59 67 71 80 89 96 as they promote leaders by affirming their roles, 96 and allow for communications on the direction and changing context of the studies. 96 Types of meetings range from informal chats (eg, over meal times and coffee breaks), 9 36 54 55 63 off-campus retreats, speed dating/networking events, 55 to seminars/workshops, 29 55 59 71 80 85 brainstorms 61 94 and 'sandpits' (meetings spread over several days).…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…13.3; green circle). This also includes scientists, because they demonstrate a high degree of commitment to the normative goal of SLM projects (Zscheischler et al 2018). Thus, the research project is considered to be a unit that proactively pushes towards sustainability by means of various measures.…”
Section: Tandi Strategic Policy Pathways In Slmmentioning
confidence: 99%